Culture and discourse: a translinguistic analysis of teletandem interactions - Zakir, Maisa de Alcantara [UNESP] (Editora Univ Pontificia Univ Catolica Rio Grande Sul-edipucrs, 2016)
The Project entitled Teletandem and Transculturality in online interaction in foreign languages by webcam has been developed since 2010 and has put learners of foreign languages in Brazil in touch with learners of Portuguese abroad in interactions via Skype. The context in which this study was developed is called semi-integrated institutional teletandem, being integrated into the curriculum of the foreign university partner in the project and non-integrated into the curriculum of the Brazilian university. This paper aims at analyzing teletandem interactions between a female student of intermediate Portuguese in a private American university and a professor who studies English as a foreign language who works at a Brazilian public university. The interactions between the participants were analyzed under the perspective of Dialogic Discourse Analysis, grounded on the work of Bakhtin and the Circle. The analysis results show the social roles identified in the participants' discourse when discussing cultural aspects.
Keywords: Institutional teletandem; Dialogic discourse analysis; Social Roles